IMPLEMENTASI AKUNTANSI KEUANGAN BERBASIS SAK ETAP (STUDI KASUS PADA UMKM BATIK DI KOTA SEMARANG) - Septriana, Ira; Vitriyani, Eva (Universitas Dian Nuswantoro Semarang, 2016)
This study was to determine how the application and understanding of the accounting method for MSMEs Batik Semarang and whether in accordance with the standards set by the government. Because of FAS EWPA set with the purpose of facilitating entities without public accountability like MSMEs in presenting the financial statements to be more relevant and informative in order to monitor the performance of business units within a single accounting period. There are 30 units of MSMEs Batik Semarang as research sample selected by convenience sampling method using qualitative descriptive analysis method. The results indicate that the perception and understanding of MSME entrepreneurs Batik Semarang on Financial Accounting Standards for Entities Without Public Accountability (FSA EWPA) was still very simple, due to the lack of entrepreneurs knowledge regarding the technical preparation of financial statements based FSA EWPA. MSMEs feel that income statement is enough, and there is a lacking sosialization by the related department like Department of Cooperatives and MSMEs Semarang in applicating the Financial Accounting Standards Entities Without Public Accountability.Keywords: MSMEs; FAS EWPA; Financial Statements